"I decide myself"- A qualitative exploration of end of life decision making processes of patients and caregivers through Advance Care Planning. - Priya Lall (Public Library of Science (PLoS), 2021)
Background The Singapore national Advance Care Planning (ACP) programme was launched in 2011 with the purpose of ensuring that healthcare professionals are fully aware of patients' treatment preferences. There is little research assessing the performance of such programmes in ethnically diverse Asian countries; hence, the purpose of this study was to qualitatively examine patients and caregivers' experiences with the ACP programme. Method We conducted interviews with 28 participants, thirteen of whom identified as proxy decision makers (PDMs) and the remainder as patients. Interviews focused on respondents' experiences of chronic illness and of participating in the ACP programme. Textual data was analysed through a framework analysis approach. Results Participants' narratives focused on four major themes with 12 subthemes: a) Engagement with Death, factors influencing respondents' acceptance of ACP; b) Formation of Preferences, the set of concerns influencing respondents' choice of care; c) Choice of PDM, considerations shaping respondents' choice of nominated health spokesperson; and d) Legacy Solidification, how ACP is used to ensure the welfare of the family after the patient passes. These findings led to our development of the directive decision-making process framework, which delineates personal and sociocultural factors influencing participants' decision-making processes. Respondents' continual participation in the intervention were driven by their personal belief system that acted as a lens through which they interpreted religious doctrine and socio-cultural norms according to their particular needs. Conclusion The directive decision-making process framework indicated that ACP could be appropriate for the Asian context because participants displayed an awareness of the need for ACP and were able to develop a concrete treatment plan. Patients in this study made decisions based on their perceived long-term legacy for their family, who they hoped to provide with a solid financial and psychological foundation after their death.